2016
DOI: 10.3390/s16010061
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Organic Compounds in Water by an Optical Absorbance Method

Abstract: This paper proposes an optical method which allows determination of the organic compound concentration in water by measurement of the UV (ultraviolet) absorption at a wavelength of 250 nm~300 nm. The UV absorbance was analyzed by means of a multiple linear regression model for estimation of the total organic carbon contents in water, which showed a close correlation with the UV absorbance, demonstrating a high adjusted coefficient of determination, 0.997. The comparison of the TOC (total organic carbon) concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Many studies indicated that machine learning has potential for the analysis of single or multi-wavelength spectral data [ 10 , 20 , 21 , 22 , 23 ]. For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water. A partial least square (PLS) regression model was developed by Carré et al [ 21 ] to establish a relationship between spectral data and total suspended solids (TSSs), turbidity, and chemical oxygen demand (COD) in reclaimed water.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicated that machine learning has potential for the analysis of single or multi-wavelength spectral data [ 10 , 20 , 21 , 22 , 23 ]. For instance, using UV absorbance spectrometry in the 250–300-nm region, Kim et al [ 24 ] used a multiple linear regression model to detect organic compounds in water. A partial least square (PLS) regression model was developed by Carré et al [ 21 ] to establish a relationship between spectral data and total suspended solids (TSSs), turbidity, and chemical oxygen demand (COD) in reclaimed water.…”
Section: Introductionmentioning
confidence: 99%
“…Among these results, the properties of the organics with unsaturated bonds, such as the aromatic compounds that strongly absorb UV light in the optimum wavelength range of 270-290 nm, showed a clear variation in absorbance for different concentrations. Moreover, saturated molecules such as inorganic compounds which are not detected in the wavelength range of 250-300 nm were also considered [16]. The absorption spectra measured ten times for each sample in the UV-LED spectroscopy system are shown in figures 3(d)-(f).…”
Section: Resultsmentioning
confidence: 99%
“…In figure 4, a best-fit line was drawn through the points of the calculated concentrations. In addition, each adjusted coefficient for the determination of R figure 4(d)), implying that the concentrations of the samples can be determined with accuracies of 99.3%, 99.2%, 95.3%, and 97.8%, respectively [16,18].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, because of some drawbacks, such as complex sample pretreatment course, long measurement period, and the requirement of chemical reagents, these systems are not suitable for applications facing sudden pollution accidents. UV-visible spectroscopy has been attracting growing attention in this application field with its advantages of fast response, in-situ multi-parameter analysis, no secondary pollution, and low maintenance costs [3,4,5]. Existing studies on water quality monitoring with UV-visible absorption spectra include building analytical models for certain parameters, such as total organic carbon (TOC) and chemical oxygen demand (COD) [6,7,8], correcting turbidity influences [9], denoising spectral data [10,11], and developing spectral compression approaches [12].…”
Section: Introductionmentioning
confidence: 99%